2007
DOI: 10.1111/j.1365-2249.2007.03484.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of lipopolysaccharide- and tumour necrosis factor-α-induced interleukin (IL)-8 expression by glucocorticoids involves changes in IL-8 promoter acetylation

Abstract: SummaryThere is accumulating evidence that the transrepressional effect of glucocorticoids in down-regulating proinflammatory gene expression might be regulated by an action on histone acetylation. To investigate this, we studied the effect of two glucocorticoids (dexamethasone and triamcinolone acetonide) on reducing lipopolysaccharide (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 28 publications
3
20
0
1
Order By: Relevance
“…In our study, we showed in human macrophages that chromatin remodeling occurs as a consequence of HIV-1 ssRNA-induced TLR8 activation, leading to TNF␣ release. These results are consistent with those in peripheral blood mononuclear cells and mouse macrophages in which dependence of TLR4-induced increase in pro-inflammatory cytokine release is dependent on chromatin remodeling (39). In addition to the modifications described by Tsaprouni et al (39), we found that histone 3 lysine 4 (H3K4me3) methylation was also markedly increased, with concomitant decrease in histone 3 lysine 27 (H3K27me3) methylation.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we showed in human macrophages that chromatin remodeling occurs as a consequence of HIV-1 ssRNA-induced TLR8 activation, leading to TNF␣ release. These results are consistent with those in peripheral blood mononuclear cells and mouse macrophages in which dependence of TLR4-induced increase in pro-inflammatory cytokine release is dependent on chromatin remodeling (39). In addition to the modifications described by Tsaprouni et al (39), we found that histone 3 lysine 4 (H3K4me3) methylation was also markedly increased, with concomitant decrease in histone 3 lysine 27 (H3K27me3) methylation.…”
Section: Discussionsupporting
confidence: 92%
“…It is known that suppression of TNF-α-induced IL-8 expression by glucocorticoids involves changes in IL-8 promoter acetylation (Tsaprouni et al, 2007). As shown in Figure 6, IPs with antibody against acetylated histone H4 revealed a marked enrichment of the IL-8 promoter DNA after TNF-α treatment.…”
Section: Grβ Overexpression Inhibit Tnf-α-induced Histone H4 Acetylatmentioning
confidence: 87%
“…Chromatin remodeling following histone acetylation at the specific gene promoter site is a major transcriptional regulatory mechanism that allows transcription factors to bind to specific gene promoters, initiating gene transcription. Tsaprouni et al (2007) reported that the ability of TNF-α to induce IL-8 expression in monocyte and T cell lines is regulated by changes in histone acetylation. Our data show that overexpression of GRβ did not show any negative effect on the glucocorticoid-induced transrepression, expression of mRNA, and secretion of IL-8, rather it looked like that GRβ had its own weak transrepressive activity, while it caused inhibition of glucocorticoid-induced transactivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ez is jól mutatja, hogy a hiszton acetiláció a génexpressziós mintázatokat a konkrét stimulus alapján szabályozza (Schmeck, 2005). Így, például LPS esetén is megfigyelhető a CXCL8 expressziójának növekedése, ami a H4 hiszton acetilációs szintjének emelkedésével jár együtt (Tsaprouni, 2007).…”
unclassified